2020
DOI: 10.1590/pboci.2020.086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TNF-α and IL-1β Concentrations in Gingival Crevicular Fluid During Early Alignment Stage of Orthodontic Treatment in Adults and Adolescents

Abstract: To compare the levels of TNF-α and IL-1β in the gingival crevicular fluid (GCF) during early leveling stage of orthodontic treatment. Material and Methods: This study was carried out on 20 orthodontic patients, including 10 teenagers and 10 adults. Before bonding, GCF was collected with a paper strip in gingival sulcus of maxillary right central incisor on the disto labial aspect for 60 seconds, followed by bonding and insertion of initial 14 NiTi archwire. GCF collection was repeated 24 hours, 7 days, and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Many studies have shown that age and gender have no effect on GCF flow rate, volume, and content (37)(38)(39). In our study, although gender had no effect on GCFV, unlike in other studies, a negative correlation was observed between age and GCFV.…”
Section: Discussioncontrasting
confidence: 89%
“…Many studies have shown that age and gender have no effect on GCF flow rate, volume, and content (37)(38)(39). In our study, although gender had no effect on GCFV, unlike in other studies, a negative correlation was observed between age and GCFV.…”
Section: Discussioncontrasting
confidence: 89%
“…Considering the involvement of general scarcity of information in this regard, especially in the dental field in Iran, and in continuing our interest in medical research [24][25][26][27] and most of the published articles on occupational hazards are in nurses and articles related to occupational hazards in dentists are based on skeletal problems and burnout. Therefore, as there are no studies on occupational hazards of dentists in Kerman covering most of occupational hazards and evaluating the awareness of occupational hazards can help identify the most common problems of dentists, this study was conducted to examine the frequency of occupational hazards in general dentists in Kerman (South East of Iran).…”
Section: Introductionmentioning
confidence: 99%
“…In continuing our interest in medical research [17][18][19] and given the shortage of studies on the frequency of self-medication in dentistry students and the lack of study on dentistry students in Kerman and due to the situation of people in the Covid-19 pandemic and the imposed restrictions due to the existence of quarantine and minimal visits to medical centers, that can increase the possibility of self-medication, the present study aims to evaluate frequency of self-medication among dentistry students of basic sciences and pre-clinics who did not pass the pharmacology course.…”
Section: Introductionmentioning
confidence: 99%